PENGARUH PENGETAHUAN DAN PEMAHAMAN TENTANG PERATURAN PERPAJAKAN, SOSIALISASI PAJAK, KONDISI KEUANGAN DAN EFEKTIVITAS SISTEM PERPAJAKAN TERHADAP KEMAUAN MEMBAYAR PAJAK BADAN DENGAN KESADARAN MEMBAYAR PAJAK SEBAGAI VARIABEL INTERVENING (Pada KPP Pratama Dumai & KPP Pratama Kuala Tungkal Jambi) - Liza, Sri Neva; Andreas, Andreas; Savitri, Enni (Jurnal Akuntansi (Media Riset Akuntansi & Keuangan), 2019)
This study aims to analyze the Effect of Knowledge and Understanding of Tax Regulations, Tax Dissemination, Financial Conditions and the Effectiveness of the Taxation System to Tax Paying willingness and Tax Paying Awareness as Intervening Variables. Endogenous variables in this study are Tax Paying Willingness and Tax Paying Awareness. Exogenous variables are Knowledge and Understanding of Tax Regulations, Tax socialization, Financial Conditions and effectiveness of Taxation Systems. The population of this study is corporate taxpayers in Dumai and Jambi. While the sample of this study is the corporate taxpayer registered in Directorate General of Taxes in Pratama Dumai and Pratama Kuala Tungkal Jambi are 197 respondents. Data analysis in this study used the Structural Equation Model with the warp PLS 5.0.The results of the study show that in model 1: knowledge and understanding of tax regulations and financial conditions affect the Tax Paying Awareness. Model 2: knowledge and understanding of tax regulations and tax socialization affect Tax Paying willingness. Model 3: Tax Paying Awareness intervenes in the relationship between knowledge and understanding of tax regulations on Tax Paying willingness. But the Tax Paying Awareness does not interfere with the relationship between tax socialization, financial conditions and the effectiveness of the taxation system on Tax Paying willingness. Model 4: Tax Paying Awareness affects the Tax Paying willingness.